1996
DOI: 10.1159/000237376
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE and lgG4 Immune Responses to Tetanus and Diphtheria Toxoid in Atopic and Nonatopic Children during the First Two Years of Life

Abstract: Background: In order to investigate, whether atopic and nonatopic children show differences in their specific IgE and IgG4 immune responses to tetanus (T) and diphtheria (D) antigens, we studied 538 children who had been followed from birth on and from whom records had been kept of all immunizations. Methods: The prevalence of eczema and asthma was registered at regular intervals and the cumulative incidence of symptoms was determined at 24 months of age. Total serum IgE and specific IgE to a panel of nine all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 11 publications
3
26
0
3
Order By: Relevance
“…Diphtheria/ tetanus vaccination elicits an IgE response directed against the vaccinated toxoids as part of the regular immune response, but this is exaggerated in individuals predisposed to atopy. 11 Pertussis vaccination elicits an IgE response to pertussis toxin, more pronounced after vaccination with acellular than whole cell vaccines. 12 To date, however, there is no evidence of a promoting effect extending to unrelated allergens or atopic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Diphtheria/ tetanus vaccination elicits an IgE response directed against the vaccinated toxoids as part of the regular immune response, but this is exaggerated in individuals predisposed to atopy. 11 Pertussis vaccination elicits an IgE response to pertussis toxin, more pronounced after vaccination with acellular than whole cell vaccines. 12 To date, however, there is no evidence of a promoting effect extending to unrelated allergens or atopic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Two other cross-sectional surveys, one conducted in London and one using US Third National Health and Nutrition Examination Survey data, also reported an association (163,164). In addition, some laboratory results have supported increased levels of IgE in subjects exposed to diphtheria, pertussis, and tetanus antigens (101,165,166). The Avon Longitudinal Study of Parents and Children (ALSPAC) cohort found no increased risk associated with pertussis vaccination for wheezing illnesses in young English children (84).…”
Section: Environmental and Lifestyle Factorsmentioning
confidence: 96%
“…We have shown previously that in German children of a prospectively followed birth cohort (MAS-90), considerable IgE responses are constituents of the regular immune response toward diphtheria (D) 3 and tetanus (T) immunization, however exaggerated in atopics (5,6). Pertussis (P) toxin and the chemically derived toxoid have a long tradition as an adjuvant for IgE formation against simultaneously administered Ags in animal models (7,8).…”
mentioning
confidence: 99%